Financial Risk Management of Kotamobagu City Government - Kamasi, Meity Angraini; Dilapanga, Abdul Rahman; Tarore, Steven (Technium Social Sciences Journal, 2025)
Risk assessment is part of Financial Risk Management that must be carried out on all major activities in the region with the intention of achieving regional financial management that is economical, effective, efficient, transparent and accountable. However, in practice, there are still discrepancies with the applicable provisions. This study aims to determine, analyze and describe the Financial Risk Management in Kotamobagu city government focused on the preparation of risk assessment documents. The method used is descriptive qualitative, by collecting data through interviews. The results showed that the preparation of the risk assessment document is not in accordance with applicable regulations, caused by a lack of understanding of the risk assessment mechanism, lack of responsiveness of the head of the regional apparatus in encouraging the implementation of risk assessment in accordance with the provisions, as well as the inadequate quality of the State Civil apparatus (ASN). To solve the identified problem, several steps can be taken. ASN need regular training and technical guidance to understand risk assessment mechanisms. The procedure should also be simplified to make it easier to implement. Regional heads should be given training on the importance of risk assessment, supported by transparent monitoring systems, and given incentives or sanctions in accordance with their responsibilities. ASN recruitment should be more selective, with qualifications as needed, accompanied by competency development programs. ASN workloads need to be reevaluated to ensure fair distribution, with additional job rotation or hiring options. ASN motivation and well-being can be improved through work-life balance support, performance recognition, and fair incentives. All these measures are aimed at creating good governance and increasing the effectiveness of the organization.